Cardiac findings in pediatric patients with spinal muscular atrophy types 2 and 3. Issue 1 (28th October 2020) - Djordjevic, Stefan A.; Milic‐Rasic, Vedrana; Brankovic, Vesna; Kosac, Ana; Vukomanovic, Goran; Topalovic, Mirko; Marinkovic, Dejan; Mladenovic, Jelena; Pavlovic, Andrija S.; Bijelic, Maja; Djukic, Milan; Markovic‐Denic, Ljiljana
Abstract: Background: It is unclear whether the heart is affected in pediatric patients with milder forms of spinal muscular atrophy (SMA). Therefore, we aimed to determine the presence of any cardiac abnormalities in these patients. Methods: We conducted a cross‐sectional study of children and adolescents with SMA types 2 and 3 between July 2018 and July 2019. All patients underwent a comprehensive cardiac evaluation, including history‐taking, physical examination, electrocardiography, echocardiography, measurement of cardiac biomarkers (cardiac troponin T [cTnT] and N‐terminal pro–brain natriuretic peptide [NT‐proBNP]), and 24‐hour Holter monitoring. Results: In total, 42 patients were enrolled (27 and 15 with SMA type 2 and 3, respectively). No patient had structural heart disease, except for one with mitral valve prolapse. None had signs of ventricular dysfunction on echocardiography. Both cTnT and NT‐proBNP levels were normal in all patients. Electrocardiography showed sinus tachycardia in seven patients (16.7%), and prolonged P‐R interval in one (2.4%). Holter monitoring detected benign ventricular arrhythmias in two patients (4.8%), and rare supraventricular premature beats in one. The mean 24‐hour heart rate was elevated in six patients (14.3%), whereas both the minimum 24‐hour heart rate and the maximum R‐R interval were increased in 23 (54.8%). Discussion: The prevalence of cardiac disease in pediatric patients with SMA types 2 and 3 is low; however, these patients may have increased resting heart rates. A complete cardiac history and physical examination are a useful screen. Additional cardiac investigations may be performed as needed.